Insights into the influence of digestate-derived biochar upon the microbial community succession during the composting of digestate from food waste. (March 2023) - Wang, Ning; Bai, Xinyue; Huang, Dandan; Shao, Mingshuai; Chen, Qindong; Xu, Qiyong
Abstract: The by-product from the anaerobic digestion of food waste (FW) called the digestate (DFW) needs proper disposal because of its high environmental burden. Composting can transform DFW into a nutrient-containing soil improver via a series of microbial metabolic activities. However, the long composting time and high amount of ammonia emission are the key concerns of DFW composting. In the present study, the effect of DFW-derived biochar (BC-DFW) on microbial succession and its involvement in nitrogen transformation and humification during DFW composting were investigated. The results indicated that the BC-DFW accelerated bacterial and fungal evolution, and the bacterial diversity was augmented by increasing the amount of BC-DFW. In particular, Cryomorpha, Castellaniella, Aequorivita, and Moheibacter were enriched by the addition of BC-DFW, thereby enhancing the degradation of organic matter and nitrogen transformation and increasing the germination index. The group with 25% BC-DFW contained a higher relative abundance of Cryomorpha (2.08%, 2.47%) than the control (0.39%, 1.72%) on days 19 and 35 which benefited the degradation of organic matter. The group with 25% BC-DFW quickly enhanced the growth of Nitrosomonas, thereby accelerating the conversion of ammonium-nitrogen to nitrate-nitrogen and reducing the phytotoxicity of the composting product. Graphical abstract: Image 1 Highlights: BC-DFW could accelerate bacterial and fungal succession during DFW composting. The bacterial diversity was increased with the increase of BC-DFW dosage. BC-DFW could promote the growth of Cryomorpha and Petriella genera. The enriched Nitrosomonas by BC-DFW were beneficial for nitrogen conversion.